Roman o podnebnih spremembah med znanstveno fantastiko in realnimi izkušnjami - Čeh Steger, Jožica (Jezik in slovstvo, 2024)
Literary science, like other sciences, has since the 1990s been intensively responding to anthropogenic climate change in an environmental and socio-cultural context. Climate issues have in literature been narrated in an aesthetic manner, appealing to the reader through stories, stirring emotions in the reader, inviting the reader to reflect on certain values and to behave in an environmentally friendly manner. The present study focuses on a novel about climate change, which in the framework of the environmen-tal genre occupies a space of much importance and which in the 1990s initially gained popularity in the Anglo-American linguistic context. Its structure includes elements of other genres, especially those of science fiction and thrillers. Recently, however, it has distanced itself from fantastic scenarios, moving towards realistic encounters with climate change that can be classified as environmental risk narratives, as illustrated by the example of the novel Zgodovina čebel (The History of Bees) by the Norwegian author Maja Lunde. Climate change is also presented in the novels Na Klancu by Tina Vrščaj and Pri-merljivi hektarji by Nataša Kramberger.
Keywords: climate fiction; ekološki riziko narativ; ekološki žanri; environmental genres; environmental risk narrative; novels on climate changes; podnebna fikcija; pripovedništvo; romani o podnebnih spremembah; Slovenian literature; Slovenian prose